EFEKTIVITAS PENGGUNAAN MEDIA BAGAN DALAM PEMBELAJARAN IPS KELAS VII SMP ISLAMIYAH PONTIANAK - Norman, Toni; Sulistyarini, Sulistyarini; Sastrawan, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is almed to know about the effectiveness of media frame to the ips study result at the sevent grade student in SMP  Islamiyah by using eksperiment method one group pre-tets and pos-tets. The problem of this research are : how the effectiveness of media frame to the ips at the sevent grade students in SMP Islamiyah Pontianak?. While, the part problem of this research are: how the studi result of seventh grade student before using media frame to the IPS in SMP Islamiyah Pontianak? How the effectiveness of media frame to the IPS in SMP Islamiyah Pontianak to the ips study result?. The variables of this research are using the independent and despendence variable. The independence variable of this research is the use of media frame, whereas the dependence variable of the study result of student. Resource of data in this research is ips study result at the sevent grade student in SMP Islamiyah Pontianak and the method of this research is descriptive method by using experiment method (one group pre-tets pos-tets). The colleckting data that us in this research are: direck observation technieq, interview, and documentary study. The analysis data that use in this research is: descriptive namely descriptive analysis. The result of this research showed that the media frame give good contribution in the increasing of ips study result, its looking bassed on the process and data analysis that researcher got in the criteria of analysis that analysis that researcher use namely: normality tets, mann-whitney U-tets and tets T(t-tets). Then based on the accounting of size effect showed that media frame has hight contribution to the IPS study result.  Keywords: the effectiveness of media frame, study result